Pengaruh Transformasi Digital, Kelengkapan Fasilitas Dan Disiplin Kerja Terhadap Peningkatan Pelayanan Di Kantor Camat Silima Pungga Pungga - Puja Situmorang; Darma Manalu; Kepler Sinaga (KALBISOCIO Jurnal Bisnis dan Komunikasi, 2026)
This study aims to analyze the influence of digital transformation, completeness of facilities, and work discipline on improving services at the Silima Pungga-Pungga Sub-district Office, both partially and simultaneously. The research method used is a quantitative approach with a sample of 99 respondents determined through a purposive sampling technique. Data were collected using a questionnaire and analyzed through instrument testing, classical assumption testing, multiple linear regression analysis, and hypothesis testing (t-test and F-test). The results of the study indicate that partially, the digital transformation variable has a positive and significant effect on improving services (t_{count} 4.301 > t_{table} 1.956). Completeness of facilities also has a positive and significant effect (t_{count} 3.474 > t_{table} 1.956), as does work discipline (t_{count} 5.974 > t_{table} 1.956). Simultaneously, the three independent variables significantly influence service improvement with an F_{count} value of 44.312 > F_{table} of 3.09. The results of the coefficient of determination (R^2) test show that the variables of digital transformation, completeness of facilities, and work discipline are able to explain the variation in service improvement by 58.3%, while the remaining 41.7% is influenced by other variables outside this research model. Based on these findings, it is recommended that relevant agencies continue to strengthen technology adoption, optimize facility maintenance, and maintain consistent employee work discipline to achieve excellent public service.